2021
DOI: 10.1002/jac5.1398
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' perceptions on patient care services and social determinants of health within independent community pharmacies in an enhanced services network

Abstract: BackgroundHealth care is transitioning from fee‐for‐service towards value‐based care. Community pharmacies are providing an increasing number of patient care services (PCS) that improve medication adherence, medication knowledge, and overall patient health. The provision of these services may differ based on the socioeconomic characteristics of the patient population. There is a lack of information on PCS delivery in independent community pharmacies and how these services are provided to underserved population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Currently, its implementation has only been studied in the community and outpatient settings. 21,22 In 1 study, 2 pharmacists working in an outpatient behavioral health clinic assessed their patients for SDOH during comprehensive medication management visits. 21 Some of the barriers they encountered included limited time, insufficient staff, and documentation of findings in the electronic health record.…”
Section: Opportunities For Pharmacists To Address Sdohmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, its implementation has only been studied in the community and outpatient settings. 21,22 In 1 study, 2 pharmacists working in an outpatient behavioral health clinic assessed their patients for SDOH during comprehensive medication management visits. 21 Some of the barriers they encountered included limited time, insufficient staff, and documentation of findings in the electronic health record.…”
Section: Opportunities For Pharmacists To Address Sdohmentioning
confidence: 99%
“…One survey study analyzed community pharmacists' willingness to adapt their workflow to accommodate screening for SDOH and found that 47.7% of survey respondents were willing to allocate more time and hire additional staff to be able to conduct SDOH screenings, provided they were reimbursed for these services. 22 To overcome the knowledge barrier, pharmacists need training on SDOH and programs available in their communities to mitigate some of the social problems patients share during a visit. Examples of SDOH screening tools are available in Table 2.…”
Section: Opportunities For Pharmacists To Address Sdohmentioning
confidence: 99%